THE USE OF FACEBOOK GROUP IN SPEAKING FOR ACADEMIC PURPOSES COURSE - Nurperdana, Hendra (2014)
The research entitled "The Use of Facebook Group in Speaking for Academic Purpose Course" attempted to investigate the students' perception toward the use of Facebook group in Speaking for Academic Purpose course and the perceived advantages and disadvantages from the use of Facebook group in Speaking for Academic Purpose course. The research was conducted in one of state universities in Bandung, West Java. The research employed a case study in which the data were gained by giving questionnaire to the students, interview with the students and lecturer and document analysis from Facebook group. The data later were analysed using the theories from Jordan (2009), Thornbury (2009), Zahidi et al. (2011) and Yunus & Salehi (2012). From the findings, the research found that students' perception toward the use of Facebook group was mostly positive. The advantages are the students stated that they were able to prepare speech, to learn new vocabulary, to get feedback from lecturer and peers, to get encouragements, and to have a less threatening ambiance in using language for expressing ideas. The disadvantages are the students claimed that they were distracted to play rather than to study in Facebook, they need advance guidance from lecturer and the rare availability of internet connection. Keywords: facebook group, speaking for academic purpose course (SAP course)